Controllable synthesis of SnS2 flakes and MoS2/SnS2 heterostructures by confined-space chemical vapor deposition. Issue 13 (25th March 2021) - Fu, Quangui; Mo, Haoxin; Ostrikov, Kostya (Ken); Gu, Xiaofeng; Nan, Haiyan; Xiao, Shaoqing
Abstract : A halogen salt-assisted confined-space CVD method is used for the controllable synthesis of SnS2 flakes, which are parallel to the substrate and have the characteristics of better crystallinity and fewer S vacancies. Abstract : Two-dimensional (2D) group-IV metal dichalcogenides (GIVMDs) like chalcogenide tin disulfide (SnS2 ) have received widespread attention due to their diverse crystal structures, strong light absorption capacity and excellent photoelectric properties. However, the CVD growth of GIVMDs like SnS2 remains challenging because GIVMDs tend to grow in out-of-plane directions. Here, we develop a halogen salt-assisted confined-space CVD method for the controllable synthesis of SnS2 flakes, which are parallel to the substrate and have the characteristics of better crystallinity and fewer S vacancies. The SnS2 FET devices exhibit a mobility of 0.39 cm 2 V −1 s −1 and an on/off ratio of 10 4 . The corresponding SnS2 photodetectors show a responsivity of 16 mA W −1 and a response time of 20 ms. We further utilize such a halogen salt-assisted confined-space CVD method to prepare vertical double-layer MoS2 /SnS2 heterostructures with good uniformity and high quality by a one-step process. The salt-assisted and confined space CVD approach provides a reliable method for the controllable synthesis of 2D GIVMDs as well as their vertical heterostructures.